The effect of the Gardens of Ideas strategy in acquiring economic concepts for sixth-grade literary students and developing their future thinking (Journal of Humanities and Social Sciences Research, 2023)
The current research aims to identify (the effect of the Gardens of Ideas strategy in acquiring economic concepts for sixth-grade literary students and developing their future thinking). For girls, this sample was randomly divided into two groups, one of them was an experimental group that included (30) students who studied the subject of economics principles using the Gardens of Ideas strategy, and the other was a control group consisting of (30) students, who studied the same subject in the traditional way. Before starting the experiment, the researcher was keen to ensure that the students of the two research groups were statistically equal in a number of variables that are believed to affect the safety of the experiment, and these variables are: (the chronological age of the students calculated in months, the future thinking test). As for the research tool, the economic concepts acquisition test consisted of (33) items of a multiple-choice type, and verified its validity and stability, as well as conducting statistical analyzes of its paragraphs. Calculating the validity and reliability of this test, and the results showed that the experimental group outperformed the control group in the test of acquiring economic concepts and the test of future thinking.